2010
DOI: 10.1002/cjce.20448
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of enhancement factor for mass transfer coefficient in regular packed liquid–liquid extraction columns

Abstract: Mass transfer coefficients are one of the most important parameters for the design of liquid-liquid extraction columns. The mass transfer coefficients of single drops in a pilot structured packed column have been measured using toluene/acetic acid/water and n-butyl acetate/acetic acid/water systems. Current research shows that theoretical models have failed to predict mass transfer coefficient precisely and are not reliable for design. In this work an empirical correlation for prediction of enhancement factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Since the results of the present research showed that nanoparticles do not show significant influence on the hydrodynamic parameters such as interfacial area, it seems that the effect of nanoparticles on extraction efficiency is due to the internal turbulence of drops. The slope of equilibrium curve (m), within the used concentration range in this work is low (m $ 0.075) and mass transfer resistance exists mainly in the organic phase [47][48][49]. It can be justified, considering the Whitman two film theory, where the overall mass transfer resistance is obtained from sum of the local mass transfer resistance in phases, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Since the results of the present research showed that nanoparticles do not show significant influence on the hydrodynamic parameters such as interfacial area, it seems that the effect of nanoparticles on extraction efficiency is due to the internal turbulence of drops. The slope of equilibrium curve (m), within the used concentration range in this work is low (m $ 0.075) and mass transfer resistance exists mainly in the organic phase [47][48][49]. It can be justified, considering the Whitman two film theory, where the overall mass transfer resistance is obtained from sum of the local mass transfer resistance in phases, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, when there is mass transfer from the continuous phase to the dispersed phase, smaller drops are produced in comparison to the same condition without mass transfer. In fact, because of the consequent interfacial tension gradient, the interface movement of the drop and the inner circulation generated into the drop gain the same direction . Therefore, this mass transfer path leads to increase on the interface deformations, consequent deformation of drops, and higher drop breakage.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, because of the consequent interfacial tension gradient, the interface movement of the drop and the inner circulation generated into the drop gain the same direction. [44][45][46] Therefore, this mass transfer path leads to increase on the interface deformations, consequent deformation of drops, and higher drop breakage.…”
Section: Influence Of Pulsation Intensity On the Mean Drop Sizementioning
confidence: 99%
“…Therefore, mass transfer resistance exists totally in the dispersed phase, that is, K od ≈ k d . 8,20 In an attractive method in modeling which has been adopted, the molecular diffusivity (D d ) in Newman's equation: where is the enhancement factor and empirical correlations are presented to predict its value. Sherwood et al 21 were first to use this approach, pointing out that the equation for radial diffusion in a rigid sphere 22 may be used for mass transfer in all kinds of drops if the molecular diffusivity is multiplied by an empirical factor ( ).…”
Section: Mass Transfer Investigationsmentioning
confidence: 99%